2020
DOI: 10.1021/acs.est.0c02755
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Demonstration and Preliminary Techno-Economic Analysis of an Onsite Wastewater Treatment System

Abstract: Providing safe and reliable sanitation services to the billions of people currently lacking them will require a multiplicity of approaches. Improving onsite wastewater treatment to standards enabling water reuse would reduce the need to transport waste and fresh water over long distances. Here, we describe a compact, automated system designed to treat the liquid fraction of blackwater for onsite water reuse that combines cross-flow ultrafiltration, activated carbon, and electrochemical oxidation. In laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…This value is similar to what we report here for total P concentrations in macerated toilet wastewater, but also aligns well with our previous report of reactive P in toilet effluent. 14 Another recent study by Reynaert et al 27 reported 36.2 mg L −1 average soluble phosphate “PO 4 ” concentration in toilet wastewater influent from a urine-diverting toilet with solids separated from the flush water. While the use of the “PO 4 ” unit is ambiguous, the analytical test used (Spectroquant) appears to give results in units of PO 4 -P. This would indicate that the average influent concentration in this study was 36.2 mg L −1 PO 4 -P or 111 mg L −1 PO 4 3− , and the nominal average concentration in the treated clean water tank is 25.4 mg L −1 PO 4 -P or 77.9 mg L −1 PO 4 3− , 27 which would be unable to meet water reuse or discharge standards with nominal effluent P concentration limits (eg, <1 mg L −1 P in India).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This value is similar to what we report here for total P concentrations in macerated toilet wastewater, but also aligns well with our previous report of reactive P in toilet effluent. 14 Another recent study by Reynaert et al 27 reported 36.2 mg L −1 average soluble phosphate “PO 4 ” concentration in toilet wastewater influent from a urine-diverting toilet with solids separated from the flush water. While the use of the “PO 4 ” unit is ambiguous, the analytical test used (Spectroquant) appears to give results in units of PO 4 -P. This would indicate that the average influent concentration in this study was 36.2 mg L −1 PO 4 -P or 111 mg L −1 PO 4 3− , and the nominal average concentration in the treated clean water tank is 25.4 mg L −1 PO 4 -P or 77.9 mg L −1 PO 4 3− , 27 which would be unable to meet water reuse or discharge standards with nominal effluent P concentration limits (eg, <1 mg L −1 P in India).…”
Section: Resultsmentioning
confidence: 99%
“…We reported in a previous publication total P values of system effluent of 8.3 and 21.5 “mg P L −1 ” 5 that we now suspect were measured omitting the heating step; thereby, those values represent only the orthophosphate as opposed to the total P. In a different publication, 13 we reported values of “P,” without specifying the form (which was orthophosphate) nor clarifying the reporting units (mg L −1 P). In another recent paper, 14 we did specify in the methods section that both reactive P and total P were reported in units of “mg L −1 PO 4 3− .” However, table columns and figure axes in that work were labelled only as “mg L −1 ” for both reactive P and total P. For added clarity in the future, we will explicitly include the full unit “mg L −1 PO 4 3− ” or “mg L −1 P” in all tables and figure axes, as demonstrated in the present work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of basic reactor configurations (e.g., continuous stirred tank reactors, CSTRs), as well as conventional (e.g., the activated sludge process) and emerging (e.g., anaerobic membrane bioreactor) technologies have been implemented in QSDsan. Additionally, a growing number of sanitation and resource recovery systems (e.g., the Biogenic Refinery, 57 the Reclaimer system 58 ) have been developed and included in the EXPOsan repository. Lists of developed process models, 59 unit operations, 60 and systems 61 can be found in QSDsan's documentation page with links to the source codes.…”
Section: Groundwork Toward An Open and Community-led Platformmentioning
confidence: 99%